Antibacterial Activity of Streptomyces Tunisiensis Mg520500 Isolated from Soil Samples - Moghannem, Saad AM (The Asia Journal of Applied Microbiology, 2018)
In the present study seven agriculture soil samples were collected from Dakahlia Governorate, Egypt. Twenty five actinomycete isolates were purified and selected according to their culture characteristics on starch nitrate agar medium. These purified isolates were examined for antibacterial activity against multidrug resistant bacteria (MDRB). Gram positive (E. faecalis and MRSA) and Gram negative E. coli. Among all tested actinomycete isolates only SA-13 isolate could inhibit the growth of all tested bacteria. All morphological, physiological and biochemical results of SA-13 isolate indicated that it belongs to the genus Streptomyces. The comparative analysis of 16S rDNA gene sequence and phylogenetic relationship showed that SA-13 isolate lies with strain Streptomyces tunisiensis CN-207. SA-13 submitted to the GenBank NCBI with the accession number, MG520500. Different optimization parameters were studied to enhance the antibacterial activity. The optimum conditions were temperature 30ºC, pH range7-8, inoculum size 6% v/v on modified riched medium and shaking at 200rpm. Cytotoxic activity of crude extract showed IC50 200µg/ml. Our results proves that; this isolate exhibit antibacterial activity against MDRB. Additional studies of purification and identification of bioactive compound may be useful for discovering a novel antibacterial compound.